Standardize routine angiography assessment of leg vasculatures before fibular flap harvest: lessons of congenital and acquired vascular anomalies undetected by color Doppler and physical examinations. (December 2021) - Ma, Chunyue; Wang, Lei; Tian, Zhuowei; Qin, Xingjun; Zhu, Dan; Qin, Jinbao; Shen, Yi
Background: Fibular flaps have been widely used for mandibular and maxillary reconstructions. On occasion, anatomical variants of fibular arteries (FA) will be encountered. Purpose: Although anatomical variants of FA during fibular harvest have been reported, controversy exists regarding whether simple color Doppler ultrasonography (CDU) and physical examinations (PE) are sufficient for early preoperative detection. Material and Methods: A 10-year retrospective analysis in our department was performed to find the patients with various FA anomalies confirmed by computed tomography angiography (CTA) or intraoperative findings. Results: A total number of 19 FA anomalies were found either pre- or intraoperatively in 16 patients, in whom three cases were with bilateral FA variants. Type IIIC variants, also called arteria peronea magna (great peroneal artery), were confirmed in two legs, while the majority (13 legs) had type IIIA hypoplastic/aplastic posterior tibialis arteries (PTA). Four legs had new type IIID (low FA and PTA bifurcations). Preoperative CDU and PE only suspected anomalies in two legs. Six cases proceeded with using the affected fibulas, within whom vascular grafts were used in half of them for lengthening the FA pedicle. Local ischemia, partial soleus muscle necrosis, and claudication were reported in one. Conclusions: Routine CTA before every fibular harvest, rather than simple PE and CDU, should be added for screening contraindications and ensuring safety for fibular flap harvest.